2022
DOI: 10.3390/ijms23179769
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Relapse Prevention of Typical and Atypical Optic Neuritis

Abstract: Optic neuritis (ON) is an inflammatory condition involving the optic nerve. Several important typical and atypical ON variants are now recognized. Typical ON has a more favorable prognosis; it can be idiopathic or represent an early manifestation of demyelinating diseases, mostly multiple sclerosis (MS). The atypical spectrum includes entities such as antibody-driven ON associated with neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD), chronic/relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 191 publications
0
11
0
6
Order By: Relevance
“…Appropriate and timely diagnosis is essential to rapidly decide on the appropriate treatment, maximize visual recovery, and minimize recurrences. Saitakis and Chwalisz [ 8 ] review the currently available state-of-the-art treatment strategies for many of these forms of optic neuritis, both in the acute phase and in the long term. The authors also discuss emerging therapeutic approaches and novel steps in the direction of achieving remyelination.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate and timely diagnosis is essential to rapidly decide on the appropriate treatment, maximize visual recovery, and minimize recurrences. Saitakis and Chwalisz [ 8 ] review the currently available state-of-the-art treatment strategies for many of these forms of optic neuritis, both in the acute phase and in the long term. The authors also discuss emerging therapeutic approaches and novel steps in the direction of achieving remyelination.…”
Section: Reviewsmentioning
confidence: 99%
“…As noted in the review by Saitakis and Chwalisz [ 8 ], one of the causes of acute optic neuritis, particularly that associated with simultaneous or sequential transverse myelitis, is the aquaporin 4 (AQP4) antibody-driven condition called neuromyelitis optica. Over the past decade, there have been significant advances in the biologic knowledge on NMOSD, which have resulted in the identification of variable disease phenotypes, biomarkers, and complex inflammatory cascades involved in the disease pathogenesis.…”
Section: Reviewsmentioning
confidence: 99%
“…A single demyelinating event failing to meet diagnostic criteria for MS, NMOSD, or MOGAD is referred to as clinically isolated syndrome (CIS). Some experts advocate for early treatment of CIS in patients deemed to be at high risk of conversion to MS [8 ▪▪ ], and some disease-modifying therapies (DMT) for MS have been approved for the chronic treatment of both MS and CIS. Several clinical trials, including the CHAMPS [9] (Controlled High-Risk Subjects Avonex Multiple Sclerosis Prevention Study), ETOMS [10] (Early Treatment of Multiple Sclerosis), BENEFIT [11] (Betaseron in Newly Emerging Multiple Sclerosis for Initial Treatment) and REFLEX [12] (REbif FLEXible dosing in early MS) trials, have demonstrated that interferon-β-1a reduces the rate of development of clinically definite MS in patients with CIS and two or more inactive typical lesions of multiple sclerosis on brain MRI.…”
Section: Idiopathic Optic Neuritis and Multiple-sclerosis Associated ...mentioning
confidence: 99%
“…It is not our practice to advocate for DMTs in patients with clinically isolated syndrome as not all will convert to clinically definite multiple sclerosis, potentially leading to unnecessary chronic immunomodulatory therapy. Further, there is limited data to suggest that early initiation of a DMT in patients with a diagnosis of CIS (as opposed to deferring DMT until a diagnosis of MS is reached) prevents long-term disability [8 ▪▪ ]. The studies discussed above did not specifically assess the role of those therapies in patients presenting with isolated optic neuritis and it is our practice to refer patients with 1 or more brain lesions to a neurologist with subspecialty training in demyelinating disease.…”
Section: Idiopathic Optic Neuritis and Multiple-sclerosis Associated ...mentioning
confidence: 99%
See 1 more Smart Citation